Developing new functional food and nutraceutical products - Bagchi, Debasis, 1954-; Nair, Sreejayan (Elsevier, 2017)
Developing New Functional Food and Nutraceutical Products provides critical information from conceptualization of new products to marketing, aiming to present a solid understanding of the entire process through detailed coverage of key concepts, namely innovation, regulation, manufacturing, quality control, and marketing. Chapters provide insights into market and competitive analysis, product design and development, intellectual property, ingredient sourcing, cost control, and sales and marketing strategies.- Examines key considerations in product development- Provides a streamlined approach for product development- Addresses manufacturing and quality control challenges- Includes key lessons for a successful product launch and effective marketing.